Optimalisasi Kurikulum Merdeka Belajar Dalam Pendidikan Agama Kristen: Mengintegrasikan Teknologi Digital Untuk Meningkatkan Motivasi Belajar Peserta Didik - Hendra Agung Saputra Samaloisa; Dyulius Thomas Bilo (Publisher STPKat, 2024)
This research investigates the optimization of Merdeka Belajar Curriculum in Christian Religious Education through the integration of digital technology to increase learners' learning motivation. The research methodology uses a phased library research approach, which involves searching, evaluating, and analyzing literature relevant to the topic. The results show that the integration of digital technology in Christianity learning can bring significant benefits in increasing students' learning motivation. The use of engaging and interactive digital tools and applications helps to create a more interesting and relevant learning experience for students. However, challenges such as technology accessibility and teacher readiness in utilizing digital technology also need to be considered. Therefore, this study highlights the importance of continuous training and support for teachers in integrating digital technology in Christianity learning. In conclusion, the integration of digital technology in Merdeka Belajar Curriculum is an important step in preparing learners to face the challenges of the modern world while still strengthening Christian values and beliefs.